Approximation of Functions by Dunkl-Type Generalization of Szász-Durrmeyer Operators Based on p, q-Integers. (18th March 2021) - Alotaibi, Abdullah
Abstract : In this article, our main purpose is to define the p, q -variant of Szász-Durrmeyer type operators with the help of Dunkl generalization generated by an exponential function. We estimate moments and establish some direct results of the aforementioned operators. Moreover, we establish some approximation results in weighted spaces.